Tybrind Vig : A Preliminary Report on a Submerged Ertebølle Settlement on the West Coast of Fyn - H. , Søren (Journal of Danish Archaeology, 1985)
Tybrind Vig - A Preliminary Report on a Submerged Ertebølle Settlement on the West Coast of Fyn